Prevalence, consequences and factors associated with drug use among individuals over 50 years of age in the family perspective - Barros, Gilmar Manoel de; Horta, Ana Lucia de Moraes; Diehl, Alessandra; Miranda, Romina Ortweiler da Rocha; Moura, Adaene Alves Machado de; Seleghim, Maycon Rogério; Silva, Claudio Jerônimo da; Santos, Manoel Antônio dos; Wagstaff, Christopher; Pillon, Sandra Cristina (Aging & mental health, 2021)
The aim of this study was to investigate the prevalence, consequences and factors associated with drug use among individuals over 50 years of age, from the perspective of their families, with particularly reference to cocaine use. Cross-sectional study based on secondary data with 624 family members of substance users who sought family support in 14 units of the Recomeço Família Program in São Paulo, Brazil. The participants were predominately men, aged 50 to 59 years (68%); cocaine users (inhaled and/ or smoked); living alone; with a low level of education and were unemployed. They were likely to use family money to pay for their substance use, with a history of theft and aggression against strangers, and were not in treatment. Unlike other participants [≥ 60 years (31.1%)]; who were better educated and retired. In this latter group, 32.8% are alcohol users, 14.8% cocaine users (inhaled and smoked), 32.6% has physically assaulted their family, 39.7% had assaulted someone else and 18.3% had stolen objects or money from home. The population has peculiar characteristics of vulnerability (cocaine use and violence) that remain under investigated; not only do routes into treatment for older adults (≥ 60) but appropriate treatment packages need to be developed too.